2017
DOI: 10.1080/20477724.2017.1309338
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin-B and vancomycin-associated acute kidney injury in critically ill patients

Abstract: Although patients who received Polymyxin B plus vancomycin had more favorable clinical profile and higher previous GFR, they presented a higher AKI incidence than those patients who received Polymyxin B alone. Cumulative Polymyxin B dose > 10 million IU was independently associated to AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
10
1
6
Order By: Relevance
“…In fact, overall AKI rates were similar to the average rate of 40% found in previous studies of PMB (range, 20% to 60%) (27)(28)(29)(30)(31)(32)(33)(34). The proportion of patients with renal failure in our study might be considered higher (46.3% of patients with AKI) than that described in reports of previous studies, which presented an average proportion of patients with renal failure of approximately 22% (but the average proportion ranged widely from 4% to 50%) (27)(28)(29)(30)(31)(32)(33)(34), and the onset of failure may have occurred earlier in our sample than patients in previous studies. The number of patients requiring renal replacement therapy in our cohort may also be considered high, potentially indicating a higher risk for more severe kidney damage in patients receiving these high doses, although a definitive conclusion requires a proper control group exposed to lower doses.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, overall AKI rates were similar to the average rate of 40% found in previous studies of PMB (range, 20% to 60%) (27)(28)(29)(30)(31)(32)(33)(34). The proportion of patients with renal failure in our study might be considered higher (46.3% of patients with AKI) than that described in reports of previous studies, which presented an average proportion of patients with renal failure of approximately 22% (but the average proportion ranged widely from 4% to 50%) (27)(28)(29)(30)(31)(32)(33)(34), and the onset of failure may have occurred earlier in our sample than patients in previous studies. The number of patients requiring renal replacement therapy in our cohort may also be considered high, potentially indicating a higher risk for more severe kidney damage in patients receiving these high doses, although a definitive conclusion requires a proper control group exposed to lower doses.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the literature reports on polymyxin B nephrotoxicity. 9 , 11 , 12 The results showed that polymyxin B could also cause increases in SCr, BUN, and urinary protein. As the experiment is based on the clinical adult dose of polymyxin B, 2.5 mg/kg/q24 h, converted to a dose of 18 mg/kg/q24 h for rats, the SCr and BUN levels of rats in each administration group are not particularly high; moreover, there is a significant fluctuation during the day, and the values of SCr and BUN often fluctuate in the range of high values and normal values during 5 days of continuous administration.…”
Section: Discussionmentioning
confidence: 97%
“…An independent association between duration of polymyxin use and AKI has been reported ( p = 0.037; OR 1.06; 95% CI [1.00–1.12]). With respect to the combination of nephrotoxins, Soares et al. (2017) investigated the incidence of AKI in 115 ICU patients who used polymyxin B plus vancomycin (Group I) or polymyxin B alone (Group II), showing higher incidence of AKI in Group I than in Group II (62.7% vs. 28.5%, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%